Muscle Activity in Pre-Treatment and Post-Treatment Oral Submucous Fibrosis Patients: Electromyography Study - Santosh R Patil; G. Maragathavalli; D. N. S. V. Ramesh; Mohammad Khursheed Alam (International Journal of Clinical Practice, 2022)
Background. Oral submucous fibrosis (OSMF) is a premalignant condition of insidious onset which affects the oral mucosa, pharynx, and esophagus. The muscles of mastication are known to be affected resulting in limited mouth opening. Electromyography (EMG) is a sophisticated method of measuring and evaluating muscle activity. Previously, EMG was primarily utilized in medical sciences, but it is currently being used extensively in both the medical and dentistry fields. Objectives. The aim of the study is to evaluate the electromyographic activity of masseter muscle in OSMF patients before and after treatment and to compare with healthy controls. Materials and Methods. This prospective case-control clinical study comprised 180 OSMF patients who were divided into four groups and 45 healthy individuals served as the control group. The OSMF individuals were injected with hyaluronidase 1,500 IU mixed in 1.5 ml of dexamethasone and 0.5 ml of lignocaine HCL intralesionally twice a week for one month along with a basic physiotherapy regimen consisting of mouth exercises two times daily. The control subjects were given placebo capsules. The treatment was carried out for a month and the electromyographic masseter muscle activity was evaluated among the OSMF patients and control group before and after treatment. Results. The results revealed that the electromyographic activity of master muscles in OSMF patients showed increased activity when compared with healthy controls. Patients with OSMF showed decreased muscle activity after treatment. Conclusion. When compared with healthy controls, OSMF patients had higher electromyographic activity of the masseter muscles and the muscle activity was decreased following treatment. In OSMF patients, EMG may help in determining the involvement of the mastication and facial expression muscles. It can also be used as a diagnostic tool to assess the treatment outcome of muscle activity in OSMF patients.